2020
DOI: 10.1177/2325967120s00488
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant Usage Following Anterior Cruciate Ligament Reconstruction is Associated with Increased Rate of Manipulation Under Anesthesia

Abstract: Objectives: Although uncommon, arthrofibrosis following anterior cruciate ligament reconstruction (ACLR) is considered to be a significant and disabling complication for a young, athletic population. In this study, we aimed to determine: (1) the prevalence of manipulation under anesthesia (MUA) for treatment of arthrofibrosis following ACLR (2) whether anticoagulant use following ACLR is associated with an increased risk of MUA. We anticipate that postoperative use of anticoagulants will be associated with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Postoperative anticoagulation use has been previously identified as a risk factor for increased stiffness after ACLR, likely because of formation of a postoperative hematoma as demonstrated by Malahias et al 11 Our study found that the use of anticoagulation increased the risk of preoperative stiffness 8-fold. While further research is needed to elucidate the mechanism associated with this observed risk, it may be hypothesized that anticoagulation use increases the risk of hemarthrosis and hematoma formation after the initial injury.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Postoperative anticoagulation use has been previously identified as a risk factor for increased stiffness after ACLR, likely because of formation of a postoperative hematoma as demonstrated by Malahias et al 11 Our study found that the use of anticoagulation increased the risk of preoperative stiffness 8-fold. While further research is needed to elucidate the mechanism associated with this observed risk, it may be hypothesized that anticoagulation use increases the risk of hemarthrosis and hematoma formation after the initial injury.…”
Section: Discussionsupporting
confidence: 68%
“…The resulting hemarthrosis likely results in the accumulation of inflammatory mediators resulting in prolonged inflammation that may initiate and propagate scar tissue formation leading to arthrofibrosis. 11 These findings suggest that physicians should be extremely vigilant when managing patients on anticoagulation and emphasize the importance of aggressive early ROM exercises after ACL injury to decrease the chance of preoperative stiffness. Future research should aim to better understand this modifiable risk factor, including the different risk profiles of the various types of anticoagulation and whether short-term cessation of these medications after injury can decrease one's risk of stiffness without increasing the risk for DVT or PE.…”
Section: Discussionmentioning
confidence: 97%